Farmers’ Behavioral Intention to Adopt Digital Livestock Platforms: The Mediating Role of Attitudinal Readiness - Hanefar, Shamsiah Banu Mohamad; Osman, Ismah; Mohammad, Suleiman Shlash; Razak, Mohamad Idham Md; Ridzuan, Abdul Rahim; Ozturk, Ilknur; Ratnasari, Ririn Tri; Vasudevan, Asokan (International Review of Management and Marketing, 2026)
The rapid digital transformation of agriculture has intensified the need to understand the factors influencing farmers’ adoption of digital livestock platforms, particularly in developing economies such as Malaysia. Although prior studies have largely relied on technology acceptance frameworks, limited attention has been given to how institutional pressures shape farmers’ adoption intentions. This study addresses this gap by examining the effects of coercive, normative, and mimetic pressures on behavioral intention, with attitudinal readiness serving as a mediating mechanism. Drawing on Institutional Theory, coercive pressure is represented by facilitating conditions, normative pressure by social influence and halal compliance, and mimetic pressure by perceived innovativeness, performance expectancy, and effort expectancy. Data were collected from 254 livestock farmers in Malaysia using a self-administered questionnaire and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that halal compliance, perceived innovativeness, and effort expectancy significantly enhance attitudinal readiness, whereas facilitating conditions, social influence, and performance expectancy do not show significant effects. Furthermore, attitudinal readiness significantly influences behavioral intention and mediates several relationships. The results indicate that mimetic pressures, particularly ease of use and innovativeness, exert stronger influence than coercive pressures, while normative pressures are effective mainly when aligned with religious values such as halal compliance. These findings suggest that successful adoption of digital livestock platforms depends not only on structural support but also on cognitive readiness and value congruence among farmers.